2019
DOI: 10.7554/elife.50160
|View full text |Cite
|
Sign up to set email alerts
|

Maternally regulated gastrulation as a source of variation contributing to cavefish forebrain evolution

Abstract: Sequential developmental events, starting from the moment of fertilization, are crucial for the acquisition of animal body plan. Subtle modifications in such early events are likely to have major impacts in later morphogenesis, bringing along morphological diversification. Here, comparing the blind cave and the surface morphotypes of Astyanax mexicanus fish, we found heterochronies during gastrulation that produce organizer and axial mesoderm tissues with different properties (including differences in the expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 74 publications
4
40
1
Order By: Relevance
“…4 c)—the fertilization of cavefish eggs with surface fish sperm and vice versa—provides a novel way to distinguish between traits evolved under maternal or zygotic control [ 32 ]. While most trait changes have been considered to originate zygotically, degeneration of the lens and retina, temporal differences in gastrulation, and some changes in the brain are under direct maternal control, and thus have consequences extending into the larval period [ 32 , 33 ]. The trait changes that occur via maternal effects could define early control points that broadly impact many downstream events in cavefish development.…”
Section: Major Interests and Research Questionsmentioning
confidence: 99%
“…4 c)—the fertilization of cavefish eggs with surface fish sperm and vice versa—provides a novel way to distinguish between traits evolved under maternal or zygotic control [ 32 ]. While most trait changes have been considered to originate zygotically, degeneration of the lens and retina, temporal differences in gastrulation, and some changes in the brain are under direct maternal control, and thus have consequences extending into the larval period [ 32 , 33 ]. The trait changes that occur via maternal effects could define early control points that broadly impact many downstream events in cavefish development.…”
Section: Major Interests and Research Questionsmentioning
confidence: 99%
“…Intermorph grafting will shed light on the cell autonomy and the effect of the embryonic signaling environment on previously described heterochronies, heterotopies and differences of gene expression levels of during development of Astyanax morphs (Hinaux et al, 2016;Pottin et al, 2011;Torres-Paz et al, 2019;Yamamoto et al, 2004). The combination of these grafting methods with the use of transgenic reporter lines such as the cavefish and surface fish zic1:GFP lines (Devos et al, 2019), will allow the detailed investigation of intrinsic and extrinsic factors implicated in eye specification and degeneration.…”
Section: Generation Of Chimeric Embryos By Cell Graftingmentioning
confidence: 99%
“…Symmetry breaking, axis elongation and neural specification occur despite the absence of extraembryonic signaling (Fulton et al, 2020;Schauer et al, 2020). In fish, these events are controlled maternally (Marlow, 2020;Solnica-Krezel, 2020) and A. mexicanus with its two morphotypes has become an excellent model to challenge the role of maternal determinants in embryogenesis (Ma et al, 2020(Ma et al, , 2018Torres-Paz et al, 2019).…”
Section: Generation Of Astyanax Gastruloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the morphological differences observed in the nervous system of A. mexicanus morphotypes have an early embryonic origin (Yamamoto and Jeffery, 2000;Pottin et al, 2011;Hinaux et al, 2016;Rétaux et al, 2016). In fact, recent evidence has shown that maternal determinants, present in the oocyte before fertilization and before zygotic developmental programs are initiated, have an important contribution to later phenotypes (Ma et al, 2018(Ma et al, , 2020Torres-Paz et al, 2019). Indeed, any differential composition of maternal determinants in the eggs is susceptible to lead to changes in early developmental events, such as activation of the zygotic genome, embryonic patterning and establishment of signaling centers, thus affecting later ontogenetic processes.…”
Section: Introductionmentioning
confidence: 99%